Regional Innovation Performances of Firms in Portugal - Purificación Vicente Galindo; Teresa de Noronha; Peter Nijkamp; Eric de Noronha Vaz (European Regional Science Association (ERSA), 2010)
Portuguese strategic choices led, during the last two decades, to an overall situation of some positive achievements in which the regions of Lisbon and Algarve have been the only ones to converge towards the European average growth rate. Regarding the other Portuguese regions, and despite national significant growth rates in the 1990s as well as successful dealing with the EMU, these are lagging behind the EU average in what concerns gross production, investment or employment generation. Meanwhile, one of the greatest public policy efforts was to diffuse much of the European funds across the entrepreneurial tissue. After a long pathway, it is time to evaluate firms' contribution to national and regional growth, their obstacles and consequences. For the purpose of this paper, innovation has served as a major contributor for the previously referred evaluation process. The discussion explains the present performance of Portuguese firms located throughout the country and explores those innovation determinants that have been detected by region. The analysis defines a set of regionalized firms' behavioural patterns towards innovation. Methodologically, the Logistic Biplot is applied to an extended sample of institutions. Variables such as 'Promoting knowledge', 'Management skils', 'Promoting R&D', 'Knowledge transfer', 'Promoting partnership & cooperation' and 'Orientation of public measures' have been used to design institutional regional profiles. All of them diverse in the way they combine determinants for their patterns towards the dynamics of regional innovation. Also, by creating a gradient of capacity to dynamically innovate, it was possible to analyze the innovation grade of each region in Portugal.
Keywords: 330; Innovation; Firms Performance; Regional Innovation Systems; Portugal; External Logistic Biplot